Risk Evaluation and Mitigation Strategies for Newly Detected Mysterious Dinga Dinga Virus Infection in Africa: A Narrative Review - Sabrina Sharmin; Salsabil Islam; Md. Aminul Haque; Md. Rabiul Islam (Health Science Reports)
ABSTRACT Background and Aims The Dinga Dinga Virus (DDV) has emerged as a mysterious disease gripping women in Uganda, raising alarm due to its unusual and distressing “dancing” like symptoms. These symptoms, characterized by involuntary movements resembling dance, suggest possible neurological involvement, though the exact pathogen remains unidentified. The causative agent for DDV is still unknown. We hypothesized that the possible microorganism could be a virus, bacteria, or vector‐borne origin. Therefore, comprehensive research is urgently needed to confirm its cause. Methods We performed a comprehensive literature search in Scopus and Web of Science related to the different outbreaks of viruses. We collected relevant information from appropriate articles for this review. Results The unique representation of the disease is spreading rapidly in localized areas that have the potential to escalate into a broader public health crisis. Preventive measures focused on symptom monitoring, public awareness, and isolation of suspected cases to limit transmission. Authorities emphasize hygiene practices, using personal protective equipment (PPE), and early reporting to manage the outbreak effectively. Simultaneously, global health organizations are being called to collaborate on diagnostic development, therapeutic interventions, and vaccine research. The disproportionate impact on women has brought social and cultural dynamics into the spotlight, as stigma and misinformation exacerbate the outbreak's challenges. Immediate and long‐term strategies must address these aspects by strengthening healthcare infrastructure and enhancing disease surveillance systems. Conclusion As the world recovers from the COVID‐19 pandemic, the DDV is a stark reminder of the ongoing threat of emerging infectious diseases. Proactive, science‐driven efforts are critical to understanding and mitigating this enigmatic disease, ensuring it does not escalate into another global health crisis.